Kajian Mutu Produk Tuna Steak Beku Di PT. Anping Seafood Indonesia - Miranto Stevanus Tappy; Hanny Welly Mewengkang; Eunike Louisje Mongi; Henny Adeleida Dien; Josefa Tety Kaparang; Daisy Monica Makapedua; Netty Salindeho (Sam Ratulangi University, 2023)
Histamine content is used as an indicator of tuna freshness, this study aims to analyze the quality of fresh tuna (Thunnus albacares) raw materials and the quality after becoming the final product of frozen tuna steak at PT. Anping Seafood Indonesia by calculating histamine levels and organoleptic tests. The method that will be used in this research is descriptive analysis. The organoleptic test results data from the responses of 6 panelists to the raw materials of fresh tuna were all very fresh and met the SNI 01-2346-2015 standard. The data of organoleptic test results on frozen tuna steak products in the first production, second production in the third production sample obtained nothing that exceeded the SNI standard limit. The organoleptic value of frozen tuna steak products meets the organoleptic quality requirements. Histamine levels of fresh tuna raw materials and histamine levels of frozen tuna steak products obtained from the three productions met the quality and food safety requirements (SNI 01-4485.1-2006).Keywords: Fresh Tuna, Loin, Steak, Histamine, Organoleptic